EFFECTS OF IMPULSE-ORIENTED EXPLOSIVE EXERCISES FOR ARMS AND LEGS ON BIOMECHANICAL EFFICIENCY AND PERFORMANCE OUTCOMES IN U-20 JAVELIN THROWERS - Dr. Abdulhaleem Hafedh Yaseen (Proximus Journal Publishing, 2025)
The results of the javelin world championships witnessed a remarkable improvement in the level of digital achievement by young throwers. This improvement is attributed to the development of throwers' special physical capabilities. Various training methods have been used in order to compete to get the farthest distance possible in this event. Therefore, this study was conceived to prepare explosive power exercises according to the principle of impulse and its effect on some biomechanical variables and the achievement of the youthlevel javelin throw. We prepared these exercises and applied those to (8) U-20 throwers of the Iraqi Athletics Federation. The researcherstests measured some biomechanical variables, which run as follows: the strength of the driving leg; the strength of the propelling leg; the impulse time of both the driving leg and the propelling leg; the force exerted by the throwing arm; the starting speed; the angle of performance; and the distance of achievement, The research problem was that the exercises used did not take a number of things into account. These include many variables in addition to what the athlete needs from explosive power exercises according to the principle of impulse in order to achieve appropriate technical performance, which is directly reflected on this achievement. The result shows noticeable development in the values of the measured biomechanical variables as well as achievement
Keywords: Explosive power; Impulse training; Biomechanical variables